CODESRIA Bulletin, No 1, 2020: Special Issue - Randomised Control Trials and Development Research in Africa (CODESRIA Bulletin, 2020)
In this issue Editorial ----------------------1 1. Pop Developmentalism in Africa, Grieve Chelwa -----------3 2. Involuntary Social Experimentation: Revisiting the Case for a Moratorium, Nimi Hoffmann --------------7 3. Randomised Trials as a Dead-end for African Development, Seán M. Muller --------------------------14 4. Climate Services for Smallholder Farmers Using Mobile Phones: Evidence from a Pilot Randomised Controlled Trial in North Benin, Rosaine N. Yegbemey -------21 5. Trust, Legitimacy and Community Perceptions on Randomisation of Cash Transfers, Marion Ouma ------------25